A hydrocarbon steam reforming catalyst and its preparation method and application

By using perovskite-type active components and calcium aluminate cement and other components in the hydrocarbon steam conversion catalyst, a uniformly dispersed perovskite structure is formed, which solves the problem that the catalyst is prone to carbon accumulation under high temperature and high pressure, significantly improves its resistance to carbon accumulation and thermal stability, and ensures long-term activity and stability.

CN116060014BActive Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111275016.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-29
Publication Date
2025-02-28
Estimated Expiration
2041-10-29

AI Technical Summary

Technical Problem

Existing hydrocarbon steam conversion catalysts are prone to carbon accumulation during operation, resulting in a decrease in stability and activity. Although the addition of commonly used potassium salts can improve the resistance to carbon accumulation, they are prone to loss, affecting the long-term stability of the catalyst.

Method used

Perovskite-type active components, calcium aluminate cement and alumina are used as the main components, and the perovskite structure is formed by beating and calcining through the sol-gel method to uniformly disperse the active components, and improve the catalyst's resistance to carbon deposits and thermal stability.

Benefits of technology

It significantly improves the resistance to carbon deposit and thermal stability of the catalyst, reduces the potassium loss rate, ensures the long-term activity and stability of the catalyst, and is suitable for high-temperature and high-pressure hydrocarbon steam conversion processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116060014B_ABST
    Figure CN116060014B_ABST
Patent Text Reader

Abstract

The invention belongs to the fields of petrochemical engineering, natural gas chemical technology, and catalyst manufacturing engineering technology, and specifically relates to a hydrocarbon steam reforming catalyst, and further discloses a preparation method thereof. The hydrocarbon steam reforming catalyst of the present invention uses perovskite-type active components, acid calcium cement, and α-Al2O3 as active ingredients, and reduces potassium loss in the catalyst by making potassium, magnesium, and nickel into active ingredients with a stable perovskite structure; and by introducing a structural additive with a thermal stabilizing effect or loading the perovskite-type metal oxide catalyst on a suitable carrier, the dispersion of the catalyst can be increased, and its thermal stability can be improved, so that the catalyst has good activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the fields of petrochemical engineering, natural gas chemical engineering technology and catalyst manufacturing engineering technology, and specifically relates to a hydrocarbon steam reforming catalyst, and further discloses a preparation method thereof. Background Art

[0002] Steam reforming of hydrocarbons is a method commonly used by domestic and foreign refining companies to produce hydrogen and synthesis gas. Among them, the steam reforming of light hydrocarbons is a process that uses natural gas, liquefied petroleum gas, refinery gas or naphtha as raw materials. In the process of steam reforming of hydrocarbons, at a certain water-carbon ratio, carbon deposition in the process of steam reforming of hydrocarbons is an inevitable thermodynamic process. Therefore, in order to prevent carbon deposition on the catalyst during the operation of steam reforming of hydrocarbons, the catalyst is required to have good activity, strength and stability, as well as strong anti-coking performance.

[0003] At present, there are two main ways to solve the problem of carbon deposition resistance of conversion catalysts at home and abroad: one is to improve the low-temperature activity of the catalyst as much as possible, and use alkaline carriers at the same time; the other is to add potassium salts and rely on potassium to promote the gasification and carbon removal reaction of carbon. However, although the addition of common potassium salts can improve the anti-carbon deposition performance of the catalyst, due to the disadvantage that potassium salts are easy to lose, the loss of potassium will reduce the stability of the catalyst to a certain extent, and after potassium is lost, it is easy to accumulate in the waste boiler system, corrode and scale, and block the waste boiler system.

[0004] At present, perovskite-type composite metal oxide (structural formula ABO3) catalysts are catalysts with great development potential. They are often used as catalytic combustion reactions and photocatalytic materials, but are rarely used for hydrocarbon steam reforming reactions. However, although perovskite-type metal oxide catalysts have good stability, they still have problems such as low specific surface area and easy sintering at high temperatures, which limits the application of perovskite-type catalysts to a certain extent. Summary of the invention

[0005] To this end, the technical problem to be solved by the present invention is to provide a hydrocarbon steam reforming catalyst, which has the advantages of high carbon deposition resistance, strong potassium fixation ability, good thermal stability and good activity;

[0006] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned catalyst, which adopts a sol-gel method to slurry the active component gel onto alumina. After the active component gel is calcined, a perovskite structure is generated, so that the active component is evenly dispersed on the alumina carrier, thereby effectively improving the comprehensive performance of the catalyst.

[0007] In order to solve the above technical problems, the present invention provides a hydrocarbon steam reforming catalyst, wherein the catalyst comprises the following components by weight based on the total amount:

[0008] Perovskite active component 35-45wt%;

[0009] Calcium aluminate cement 15-25wt%;

[0010] α-Al2O3 balance;

[0011] The perovskite active component has the general formula K x Mg 1-x The structure shown in NiO3, wherein x = 0.1-0.2.

[0012] Specifically, the pore volume of the catalyst is 0.30-0.50 mL / g, the bulk density is 0.85-0.95 Kg / L, and the lateral pressure strength of the catalyst is greater than 250 N / particle.

[0013] Specifically, the catalyst may have an appearance of a four-hole column, a seven-hole column, a Raschig ring, a seven-rib wheel, or the like.

[0014] The present invention also discloses a method for preparing the hydrocarbon steam reforming catalyst, comprising the following steps:

[0015] (1) taking a selected amount of the α-Al2O3, adding citric acid, and adding water to mix thoroughly to form a liquid mixture for later use;

[0016] (2) according to the selected ratio of the perovskite active component, potassium nitrate, magnesium nitrate and nickel nitrate are added to prepare a solution for later use;

[0017] (3) dropping the solution obtained in step (2) into the liquid mixture obtained in step (1), mixing thoroughly and heating to evaporate water, so that the mixture gradually changes into a gel form;

[0018] (4) drying and calcining the gel obtained in step (3) to obtain a catalyst semi-finished product for standby use;

[0019] (5) The obtained catalyst semi-finished product is crushed, and a selected amount of the acid calcium cement is added and mixed, and water is further added to mix, and then pressed into shape and cured to obtain the catalyst semi-finished product.

[0020] Specifically, the molar ratio of the amount of citric acid added in step (1) to the total amount of nitrate in step (2) is 1:2-4.

[0021] Specifically, in step (4), the temperature of the drying step is 80-150°C.

[0022] Specifically, in step (4), the calcination temperature is 500-1000°C, and the calcination time is 4-8 hours. Preferably, the calcination temperature is 700-850°C, and the calcination time is 5-10 hours. The temperature affects the formation of the active component perovskite.

[0023] Specifically, in step (5), the curing step is steam curing, and the curing time is 24-36 hours.

[0024] The invention also discloses the application of the catalyst in a hydrocarbon steam reforming process.

[0025] Specifically, the catalyst is suitable for the reformer inlet temperature of 430-600°C, outlet temperature of 700-850°C, and conversion carbon space velocity of 8000h -1 The invention relates to a hydrocarbon steam reforming process with a water-carbon ratio of 1.2-3.5 and a pressure of 2.0-4.0 MPa, for producing hydrogen or synthesis gas. Under the above conditions, the potassium loss rate of the catalyst is less than 3%.

[0026] The hydrocarbon steam reforming catalyst of the present invention uses perovskite-type active components, acid calcium cement and α-Al2O3 as active ingredients. By making potassium, magnesium and nickel into active ingredients with a stable perovskite structure, potassium loss in the catalyst can be reduced; and by introducing a structural additive with a thermal stabilizing effect or loading the perovskite-type metal oxide catalyst on a suitable carrier, the dispersion of the catalyst can be increased, and its thermal stability can be improved, thereby making the catalyst have good activity.

[0027] The hydrocarbon steam reforming catalyst of the present invention uses conventional potassium element to resist carbon deposition. On the one hand, potassium catalyzes the reaction between C and H2O, accelerating the carbon removal efficiency; on the other hand, potassium can also neutralize the acid center of the catalyst, thereby slowing down the formation of carbon. The catalyst of the present invention adds an appropriate amount of K content, that is, potassium can be used to present alkalinity, effectively neutralize the acid center of the catalyst, effectively promote the gasification reaction of water vapor and carbon, and effectively avoid the acid center of the catalyst catalyzing the carbon chain cracking of higher hydrocarbons into CH due to the high potassium content. x The free radical process effectively ensures the conversion activity of the catalyst. At the same time, the magnesium contained in the catalyst of the present invention is alkaline and has strong water absorption, so it can have a certain anti-carbon deposition effect. Moreover, the addition of magnesium can also reduce the amount of potassium added to the catalyst, ensuring that the potassium content is moderate and the effect is better.

[0028] The catalyst of the present invention has the advantages of strong potassium fixation ability, high carbon deposition resistance and high activity. Compared with industrial catalysts, the catalyst can be used at a system pressure of 3.0 MPa and a carbon space velocity of 8000 h -1 The hydrocarbon steam reforming catalysis was carried out under the process conditions of H2O / C (mol / mol) of 1.5, bed inlet temperature of 430℃ and bed outlet temperature of 720℃, which had better activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0030] Figure 1 The XRD pattern of the catalyst prepared in Example 1 of the present invention;

[0031] Figure 2 It is a schematic diagram of the process of a small-scale pressurized activity evaluation device for evaluating catalyst activity;

[0032] The reference numerals in the figure are as follows: 1-oil metering pump, 2-water metering pump, 3-vaporizer, 4-mixer, 5-tubular reactor, 6-condenser, 7-separator, 8-pressure stabilizer, 9-wet flow meter. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0034] Example 1

[0035] The method for preparing the hydrocarbon steam reforming catalyst described in this embodiment comprises the following steps:

[0036] (1) Weigh 192 g of citric acid and 142.5 g of aluminum oxide, add them to 500 mL of deionized water, mix well, and set aside;

[0037] (2) Weigh 20.2 g potassium nitrate, 205.1 g magnesium nitrate, and 290.7 g nickel nitrate into 1000 mL deionized water, mix thoroughly to form a solution, and set aside;

[0038] (3) under stirring, dropwise adding the solution in step (2) to the liquid mixture obtained in step (1) and mixing thoroughly; then heating the obtained liquid mixture to evaporate water so that it gradually turns into a gel;

[0039] (4) placing the formed gel in a drying oven, drying it at 120° C., and then placing it in an electric furnace for calcination at 750° C. for 6 h to obtain a catalyst semi-finished product;

[0040] (5) The semi-finished product obtained by the above calcination was crushed, and 69.1 g of calcium aluminate cement and an appropriate amount of water were added and mixed evenly, and then pressed into shape. After steam curing for 24 hours, the finished catalyst cat-1 was obtained.

[0041] After testing, the active component of the catalyst is K 0.2 Mg 0.8 NiO3, its XRD pattern is shown in Figure 1 shown.

[0042] Example 2

[0043] The method for preparing the hydrocarbon steam reforming catalyst described in this embodiment comprises the following steps:

[0044] (1) Weigh 96 g of citric acid and 102.5 g of aluminum oxide, add them into 500 mL of deionized water, mix well, and set aside;

[0045] (2) Weigh 10.1 g potassium nitrate, 230.8 g magnesium nitrate, and 290.7 g nickel nitrate and add them to 1000 mL deionized water to prepare a solution for later use;

[0046] (3) under stirring, dropwise adding the solution formed in step (2) to the liquid mixture obtained in step (1) and mixing thoroughly; then heating the obtained liquid mixture to evaporate water so that it gradually turns into a gel;

[0047] (4) placing the obtained gel in a drying oven, drying it at 120° C., and then placing it in an electric furnace and calcining it at 800° C. for 8 h to obtain a catalyst semi-finished product;

[0048] (5) The catalyst semi-finished product obtained by calcination was crushed, and 58.6 g of calcium aluminate cement and an appropriate amount of water were added and mixed evenly, and then pressed into shape. After steam curing for 24 hours, the finished catalyst cat-2 was obtained. The active component of the catalyst is K 0.1 Mg 0.9 NiO3.

[0049] Example 3

[0050] The method for preparing the hydrocarbon steam reforming catalyst described in this embodiment comprises the following steps:

[0051] (1) Weigh 150 g of citric acid and 169.5 g of aluminum oxide, add them to 500 mL of deionized water, mix well, and set aside;

[0052] (2) Weigh 10.1 g potassium nitrate, 230.8 g magnesium nitrate, and 290.7 g nickel nitrate and add them to 1000 mL deionized water to prepare a solution for later use;

[0053] (3) under stirring, adding the solution obtained in step (2) dropwise to the liquid mixture obtained in step (1) and mixing thoroughly; and heating the obtained liquid mixture to evaporate water so that the mixture gradually turns into a gel;

[0054] (4) placing the obtained gel in a drying oven, drying it at 120° C., and then placing it in an electric furnace and calcining it at 800° C. for 8 h to obtain a catalyst semi-finished product;

[0055] (5) After the above calcined catalyst semi-finished product was crushed, 75.3 g of calcium aluminate cement and an appropriate amount of water were added and mixed evenly, and then pressed into shape. After steam curing for 24 hours, the finished catalyst cat-3 was obtained. The active component of the catalyst is K 0.1 Mg 0.9 NiO3.

[0056] Example 4

[0057] The method for preparing the hydrocarbon steam reforming catalyst described in this embodiment comprises the following steps:

[0058] (1) Weigh 135 g of citric acid and 133 g of aluminum oxide, add them into 500 mL of deionized water, mix well, and set aside;

[0059] (2) Weigh 15.2 g potassium nitrate, 217.9 g magnesium nitrate, and 290.7 g nickel nitrate and add them to 1000 mL deionized water to prepare a solution for later use;

[0060] (3) under stirring, adding dropwise the solution obtained in step (2) to the liquid mixture obtained in step (1) and mixing thoroughly; then heating the obtained liquid mixture to evaporate water so that it gradually turns into a gel;

[0061] (4) drying the obtained gel in a drying oven at 120° C., and then calcining the gel in an electric furnace at 850° C. for 6 h to obtain a semi-finished catalyst;

[0062] (5) The calcined catalyst semi-finished product was crushed, 66.5 g of calcium aluminate cement and an appropriate amount of water were added and mixed evenly, and then pressed into shape. After steam curing for 24 hours, the finished catalyst cat-4 was obtained. The active component of the catalyst is K 0.15 Mg 0.85 NiO3.

[0063] Comparative Example 1

[0064] The preparation method of the catalyst described in this comparative example comprises the following steps:

[0065] (1) Weigh 192 g of citric acid and add it to 500 mL of deionized water to dissolve it to obtain a citric acid solution for later use;

[0066] (2) Weigh 20.2 g potassium nitrate, 205.1 g magnesium nitrate, and 290.7 g nickel nitrate and add them to 1000 mL deionized water to prepare a solution for later use;

[0067] (3) under stirring, adding the solution obtained in step (2) dropwise to the citric acid solution obtained in step (1) and mixing thoroughly; then heating the obtained solution to evaporate water so that it gradually turns into a gel;

[0068] (4) drying the obtained gel in a drying oven at 120° C., and then calcining the gel in an electric furnace at 750° C. for 6 h to obtain a semi-finished catalyst;

[0069] (5) The calcined catalyst semi-finished product was crushed, 69.1 g of calcium aluminate cement, 142.5 g of alumina and an appropriate amount of water were added and mixed evenly, and then pressed into a mold. After steam curing for 24 hours, a comparative catalyst cat-5 was obtained. The active component of the catalyst was K 0.2 Mg 0.8 NiO3.

[0070] Comparative Example 2

[0071] In this comparative example, the carbon conversion rate and potassium loss rate are compared with industrial catalyst A, the chemical composition of the catalyst is NiO% (m / m) ≥ 16, and the anti-carbon deposition performance of the catalyst is improved by directly adding potassium nephrite double salt.

[0072] Comparative Example 3

[0073] The preparation method of the hydrocarbon steam reforming catalyst described in this comparative example comprises the following steps:

[0074] (1) Weigh 192 g of citric acid and 142.5 g of aluminum oxide, add them to 500 mL of deionized water, mix well, and set aside;

[0075] (2) Weigh 30.3 g potassium nitrate, 179.5 g magnesium nitrate, and 290.7 g nickel nitrate into 1000 mL deionized water, mix thoroughly to form a solution, and set aside;

[0076] (3) under stirring, dropwise adding the solution in step (2) to the liquid mixture obtained in step (1) and mixing thoroughly; then heating the obtained liquid mixture to evaporate water so that it gradually turns into a gel;

[0077] (4) placing the formed gel in a drying oven, drying it at 120° C., and then placing it in an electric furnace for calcination at 750° C. for 6 h to obtain a catalyst semi-finished product;

[0078] (5) The semi-finished product obtained by the above calcination was crushed, and 69.1 g of calcium aluminate cement and an appropriate amount of water were added and mixed evenly, and then pressed into shape. After steam curing for 24 hours, a comparative catalyst cat-6 was obtained.

[0079] The active component of the catalyst is K 0.3 Mg 0.7 NiO3.

[0080] Experimental example

[0081] In view of the complexity of characterizing the pressurized activity of hydrocarbon steam reforming catalysts, which is a balance of multiple data indicators, the present invention uses n-hexane as raw material, selects carbon conversion rate as a reference indicator of catalyst activity, and uses a small pressurized activity evaluation device for catalyst activity evaluation. Conventional devices in the field are used. The specific structural schematic diagram is shown in the attached Figure 2 , and the use steps are well known to those skilled in the art.

[0082] The specific catalyst pressurization activity conditions are:

[0083] Catalyst particle size: 40-60 mesh;

[0084] Catalyst loading: 45mL;

[0085] Pressure: 3.0MPa;

[0086] Carbon space velocity: 10000h -1 ;

[0087] H2O / C (mol / mol): 2.0;

[0088] Bed temperature: inlet temperature 480℃, outlet temperature 700℃;

[0089] Operation time: 100h;

[0090] Carbon conversion rate = (CO content of conversion process gas (%) + CO2 content of conversion process gas (%)) / total carbon of conversion process gas (%);

[0091] Determination of potassium loss rate: quantitatively weigh a 40-50 mesh sample, immerse it in 200 mL of water, heat it under reflux for 6 hours, and determine the potassium content in the water with a flame photometer.

[0092] The carbon content in the sample discharged from the catalyst bed outlet section is determined by a carbon-sulfur analyzer.

[0093] The evaluation data results of the catalyst are shown in Table 1 below.

[0094] Table 1 Evaluation and analysis data after 100h of pressurization evaluation

[0095]

[0096] It can be seen from the data in Table 1 that the carbon conversion rate of the catalyst prepared by the present invention is comparable to that of the industrial catalyst A. After 100 hours of evaluation, the potassium loss rate and carbon content in the unloading sample of the catalyst prepared by the present invention are better than those of the industrial catalyst A. This indicates that the catalyst prepared by the present invention has good anti-carbon deposition ability, potassium fixation ability, and good activity that can be used in industrial production.

[0097] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A hydrocarbon steam reforming catalyst, characterized in that: The catalyst, calculated on a total basis, comprises the following components by weight: Perovskite active component 35-45wt%; Calcium aluminate cement 15-25wt%; α-Al2O3 remainder; The perovskite active component has the general formula K x Mg 1-x The structure shown in NiO3, wherein x = 0.1-0.

2.

2. The hydrocarbon steam reforming catalyst according to claim 1, characterized in that: The pore volume of the catalyst is 0.30-0.50 mL / g, the bulk density is 0.85-0.95 Kg / L, and the lateral pressure strength of the catalyst is greater than 250 N / particle.

3. The hydrocarbon steam reforming catalyst according to claim 1 or 2, characterized in that: The catalyst includes four-hole columnar shape, seven-hole columnar shape, Raschig ring shape and seven-rib wheel shape.

4. A method for preparing a hydrocarbon steam reforming catalyst according to any one of claims 1 to 3, characterized in that: The steps include: (1) taking a selected amount of the α-Al2O3, adding citric acid, and adding water to mix thoroughly to form a liquid mixture for later use; (2) according to the selected ratio of the perovskite active component, potassium nitrate, magnesium nitrate and nickel nitrate are added to prepare a solution for later use; (3) dropping the solution obtained in step (2) into the liquid mixture obtained in step (1), mixing thoroughly and heating to evaporate water, so that the mixture gradually changes into a gel form; (4) drying and calcining the gel obtained in step (3) to obtain a catalyst semi-finished product for standby use; (5) The obtained catalyst semi-finished product is crushed, and a selected amount of the calcium aluminate cement is added and mixed, and water is further added to mix, and then pressed into shape and cured to obtain the catalyst semi-finished product.

5. The method for preparing a hydrocarbon steam reforming catalyst according to claim 4, characterized in that: The molar ratio of the amount of citric acid added in step (1) to the total amount of nitrate in step (2) is 1:2-4.

6. The method for preparing a hydrocarbon steam reforming catalyst according to claim 4 or 5, characterized in that: In the step (4), the temperature of the drying step is 80-150°C.

7. The method for preparing a hydrocarbon steam reforming catalyst according to claim 4 or 5, characterized in that: In the step (4), the temperature of the calcination step is 500-1000° C., and the calcination time is 4-8 hours.

8. The method for preparing a hydrocarbon steam reforming catalyst according to claim 4 or 5, characterized in that: In the step (5), the curing step is steam curing, and the curing time is 24-36 hours.

9. Use of the catalyst according to any one of claims 1 to 3 in a hydrocarbon steam reforming process.

10. The use according to claim 9, characterized in that: The catalyst is suitable for the converter inlet temperature of 430-600°C, outlet temperature of 700-850°C, and conversion carbon space velocity of 8000h -1 , a hydrocarbon steam reforming process with a water-to-carbon ratio of 1.2-3.5 and a pressure of 2.0-4.0MPa, for producing hydrogen or synthesis gas.

Citation Information

Patent Citations

  • Hydrocarbon steam conversion catalyst and preparation method thereof

    CN105561990A

  • Composite metal oxide catalyst, preparation method thereof and application of composite metal oxide catalyst in catalysis of direct decomposition of nitrogen oxides

    CN113145122A